2012
DOI: 10.1039/c2em10738d
|View full text |Cite
|
Sign up to set email alerts
|

Bio-monitoring for uranium using stream-side terrestrial plants and macrophytes

Abstract: This study evaluated the abilities of various plant species to act as bio-monitors for environmental uranium (U) contamination. Vegetation and soil samples were collected from a U processing facility*.The water-way fed from facility storm and processing effluents was the focal sample site as it represented a primary U transport mechanism. Soils and sediments from areas exposed to contamination possessed U concentrations that averaged 630 mg U kg Strontium is chemically and physically similar to calcium (Ca) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Moreover, it is also necessary to consider the factor 'plant'. Indeed, it has been truly observed that concentrations of U in plants vary between species independently of soil concentrations (e.g., Caldwell et al, 2012;Saric et al, 1995;Shtangeeva, 2010). This may be due to the ability of plants to manipulate the rhizosphere conditions, regulating the acquisition of nutrients (and other substances) from the rooting soil.…”
Section: Uranium Accumulation Trend In Plantsmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, it is also necessary to consider the factor 'plant'. Indeed, it has been truly observed that concentrations of U in plants vary between species independently of soil concentrations (e.g., Caldwell et al, 2012;Saric et al, 1995;Shtangeeva, 2010). This may be due to the ability of plants to manipulate the rhizosphere conditions, regulating the acquisition of nutrients (and other substances) from the rooting soil.…”
Section: Uranium Accumulation Trend In Plantsmentioning
confidence: 96%
“…The absorption of U by the plants has been shown to be dependent upon the degree of U contamination in the soil and water (e.g., Caldwell et al, 2012), pH, temperature, soil ions, the cation exchange capacity of the soil, and organic matter content (e.g., Antosiewicz, 1992;Salim et al, 1993). Uranium speciation may also be a crucial factor, influencing U uptake by plants.…”
Section: Uranium Accumulation Trend In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear distinction between high and low pollution tolerant insect groups in river bodies compared to plankton and fish (Prabhakaran, Nagarajan, Franco, & Kumar, 2017;Sreeja, 2018). Furthermore, insects provide cheap and useful ways to bio-monitor aquatic systems than chemicals do (Abdullah, Hazwani, & Abas, 2016;Caldwell et al, 2012;Kokkali & van Delft, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, uranium, thorium, and REE levels of 630, 75, and 56500 mg kg −1 , respectively, have been detected in various surface soils, with the highest levels measured in some areas of the United States of America, Bulgaria, and China (Neves et al, 2009;Caldwell et al, 2012;Mihaylova et al, 2013;Sadeghi et al, 2013;Wang and Liang, 2015;Fiket et al, 2016;Ramos et al, 2016;Han et al, 2017;Brito et al, 2018;Kaishwa et al, 2018;Santos-Francés et al, 2018;Arome et al, 2019;Wang et al, 2019a;Freitas Rodrigo et al, 2021;Wang et al, 2022;Table 5). In sediments, U, Th, and REE values of up to 126, 12, and 4000 mg kg −1 , respectively, were detected, with the highest values measured in some areas of Malaysia, Thailand, and Japan (Zhu et al, 1997;Munksgaard et al, 2003;Borrego et al, 2005;Marmolejo-Rodríguez et al, 2007;Prego et al, 2009;Tranchida et al, 2011;Deepulal et al, 2012;Antonina et al, 2013;Kritsananuwat et al, 2014;Cordeiro et al, 2016;Sahu et al, 2016;Fiket et al, 2018b;Brito et al, 2018;El-Taher et al, 2018;El-Taher et al, 2019;Elias et al, 2019;Nascimento et al, 2019;Sivasamandy et al, 2019;Bergmann and Graça, 2020;Tanaka et al, 2020;Wu et al, 2020...…”
Section: Soil and Sedimentsmentioning
confidence: 99%